Novel Biomarkers Aid in Diagnosis of PPCM - Vinall, Phil (MD Conference Express, 2014)
Peripartum cardiomyopathy (PPCM) is a potentially life-threatening disease that is manifest as heart failure with left ventricular systolic dysfunction that occurs toward the end of pregnancy or in the months following delivery. It is associated with significant mortality and morbidity. Although its etiology has recently been the subject of much study, PPCM remains a diagnosis of exclusion. This article discusses 2 potential biomarkers for PPCM that may improve diagnosis and thus treatment outcomes.